(untitled) (Revista Direito em Debate, 2022)
The spatial criterion of incidence of the Motor Vehicle Property Tax (IPVA), associated with the taxpayer discretion to be able to indicate a home of his preference, in addition to the different rates stipulated by the respective federated entity, provides and encourages the appearance of the so-called tax war. The objective is to carry out an analysis of the legalities of the IPVA, bringing to light the problem of the lack of a Complementary Law, which creates general rules on the aforementioned tax, as well as the absence of a Federal Senate Resolution, which provides for a mandatory minimum rate. to all member states. The methodological approach used will be qualitative, focused on documentary analysis of laws and jurisprudence. The regulatory gap fosters fiscal war, which in turn compromises the integrity of the federal pact, creates legal uncertainty and harms both member states and good faith taxpayers.